An Investigation on the Crisis Management Practices of Boutique Hotels and Villas in Sri Lanka: Lessons from the COVID-19 Era - Rajapakse, Vageesha; Jayasuriya, Nisha; Senadheera, Sewwandi; Seneviratne, Nirmalee (Centre For Tourism Planning and Development, 2025)
This study investigates the key crisis experiences and coping management strategies adopted by boutique hotels and villas in Sri Lanka with specific reference to the coronavirus (COVID-19) pandemic and the subsequent economic downturn era in Sri Lanka. A qualitative research method was adopted in conducting the study. Data was gathered using eight semi-structured interviews targeting general managers of registered boutique hotels and villas in Sri Lanka, selected through the snowball sampling technique. The thematic analysis was conducted to extract the main ideas from the transcripts. The study's results revealed infrastructural discrepancies, strategy risk, and distorted supply chains as three key crisis experiences encountered by boutique hoteliers in Sri Lanka during the period under study. Three key coping strategies were discovered as those predominantly used by boutique hoteliers during the crises, stressing the importance of product diversification, marketing efforts, and revamping supply chains. This study urges hoteliers to enhance crisis resilience through strategic adjustments, including restructuring supply chains via local partnerships for authenticity and cost benefits. It also raises caution to governments, emphasizes proactive planning for national resilience, especially in infrastructure, and advocates for active government involvement/participation in the tourism sector.